Noninvasive Detection of Extracellular pH in Human Benign and Malignant Liver Tumors Using CEST MRI - Tang, Yanyan; Xiao, Gang; Shen, Zhiwei; Zhuang, Caiyu; Xie, Yudan; Zhang, Xiaolei; Yang, Zhongxian; Guan, Jitian; Shen, Yuanyu; Chen, Yanzi; Lai, Lihua; Chen, Yuanfeng; et al. (Frontiers in Oncology, 2020)
Keywords: Extracellular pH, Ioversol, CEST MRI, Hepatic carcinoma, Hepatic hemangioma. Purpose: In this study, we aimed to use 3T magnetic resonance imaging (MRI), which is clinically available, to determine the extracellular pH (pHe) of liver tumors and prospectively evaluate the ability of chemical exchange saturation transfer (CEST) MRI to distinguish between benign and malignant liver tumors. Methods: Different radiofrequency irradiation schemes were assessed for ioversol-based pH measurements at 3T. CEST effects were quantified in vitro using the asymmetric magnetization transfer ratio (MTRasym) at 4.3 ppm from the corrected Z spectrum. Generalized ratiometric analysis was conducted by rationing resolved ioversol CEST effects at 4.3 ppm at a flip angle of 60°and 350°. Fifteen patients recently diagnosed with hepatic carcinoma and five patients diagnosed with hepatic hemangioma (1 male; mean age, 48.6 [range, 37–59] years) were assessed. Results: By conducting CEST pH MRI, the pH of ioversol was determined to be 6.0–7.2 at 3T in vitro. In vivo, ioversol signal intensities in the tumor region in patients with hepatic carcinoma were attenuated (mean ± standard deviation, 6.66 ± 0.19), whereas they were stabilized (mean ± standard deviation, 7.34 ± 0.09) among patients with hepatic hemangioma. The lesion size was similar between CEST pH MRI and T2-weighted imaging. In liver cancer, Conclusion: Ioversol CEST pH MRI can detect extracellular pH in human liver tumors and can provide molecular-level diagnostic tools for benign and malignant liver tumors at 3T.